Hepatitis C virus prevalence in Belgium. (4th October 2021) - Michaelis, Martin; Van Baelen, Luk; Van der Heyden, Johan
Abstract: Reliable hepatitis C prevalence estimates are crucial for a good follow-up of the indicators to eliminate hepatitis by 2030 as set by the World Health Organization. In Belgium, no recent national population-based hepatitis C virus (HCV) seroprevalence estimate is available. The current study estimated HCV prevalence as part of the first Belgian Health Examination Survey, which was organized in 2018 as a second stage of the sixth Belgian Health Interview Survey. This national population-based cross-sectional study resulted in a weighted national HCV seroprevalence of 0.02% (95% CI 0.00–0.07%). The results show a much lower HCV seroprevalence compared to previous studies.